2017
DOI: 10.3389/fcell.2017.00101
|View full text |Cite
|
Sign up to set email alerts
|

Therapy for Cancer: Strategy of Combining Anti-Angiogenic and Target Therapies

Abstract: The concept that blood supply is required and necessary for cancer growth and spreading is intuitive and was firstly formalized by Judah Folkman in 1971, when he demonstrated that cancer cells release molecules able to promote the proliferation of endothelial cells and the formation of new vessels. This seminal result has initiated one of the most fascinating story of the medicine, which is offering a window of opportunity for cancer treatment based on the use of molecules inhibiting tumor angiogenesis and in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
56
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(56 citation statements)
references
References 214 publications
(248 reference statements)
0
56
0
Order By: Relevance
“…Several preclinical studies revealed the anti-angiogenic benefits when inhibiting TGFβ in CRC, HCC, and GBM xenografts (189)(190)(191). This offers the rationale to combine TGFβ inhibitors with anti-VEGF agents (192).…”
Section: Targeting Transforming Growth Factor-β To Overcome Resistancmentioning
confidence: 99%
“…Several preclinical studies revealed the anti-angiogenic benefits when inhibiting TGFβ in CRC, HCC, and GBM xenografts (189)(190)(191). This offers the rationale to combine TGFβ inhibitors with anti-VEGF agents (192).…”
Section: Targeting Transforming Growth Factor-β To Overcome Resistancmentioning
confidence: 99%
“…Angiogenesis is one of the important hallmarks of cancer [ 24 ], and ER is an essential agonist and inducer of angiogenesis signaling pathways [ 25 ]. Angiogenesis can be inhibited by the VEGFR-2 signaling pathway inhibitors like sorafenib or sunitinib.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, the anti-VEGF-A drug bevacizumab failed to improve patients’ overall survival as a monotherapy at first, thus it was combined with paclitaxel for the HER2 - metastatic BC and got Food and Drug Administration (FDA) approval, before withdrawal of this combination again due to efficacy issues and acquired resistance. Thus, new combinations that can show stronger effects on major hallmarks of cancer, like the cell cycle and apoptosis, are needed to overcome the drawbacks of the previous anti-VEGFR combinations [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…Angiogenic activators include angiopoietins, CCL2, EGFL6, endothelins, FGF, HIF1, IGF1, MMPs, PDGF, TGF, VEGF, and et al (48)(49)(50)(51)(52)(53)(54)(55)(56). On the other hand, angiostatin, endostatin, TSP1, and PAI2 are among the endogenous inhibitors of angiogenesis (57)(58)(59)(60).…”
Section: Angiogenesis In Prostate Cancermentioning
confidence: 99%
“…Due to the striking pathological similarity between SCLC and NEPC, it is likely that, for NEPC, finding the right combinations of anti-angiogenesis and other therapies will be key to achieve significant efficacy for NEPC. Several strategies of combining anti-angiogenic regimens with targeted/chemo/immune therapies have been or are being tested clinically in several cancer types (59). These strategies include combining different anti-angiogenic regimens, simultaneously inhibiting angiogenesis and driving oncogenes, or combining anti-angiogenic regimens with immunotherapy.…”
Section: Anti-angiogenesis Therapy and Combination Treatments For Nepc?mentioning
confidence: 99%